Features of the Composition of the Colon Microbiota in Children of the First Year of Life with Functional Gastrointestinal Disorders - E. V. Grigorova; L. V. Rychkova; L. F. Sholokhov; N. L. Belkova; U. M. Nemchenko; E. A. Kungurtseva; N. M. Voropaeva; M. V. Savelkayeva (Acta Biomedica Scientifica)
Background. The development of functional gastrointestinal disorders (FGID) in children, especially in the first year of life, is a key factor in the formation of an altered colon microbiota and its formation in older age. The article presents both clinical-detailed anamnesis, symptoms of FGID, and bacteriological characteristics – qualitative and quantitative composition of the colon microbiota in children of the first year of life.Aim: to determine the features of the colon microbiota in children of the first year of life with FGID.Materials and methods. The objects of the study were children of the first year of life (n = 28) with a diagnosis of FGID established by a gastroenterologist. The material was divided into two comparison groups, depending on the age of the subjects: the first group included stool sample cultures of children aged from birth to 6 months (n = 17), the second – from 6 to 12 months (n = 11). The bacteriological study of the quantitative and qualitative composition of the contents of the colon was performed using standard methods.Results. According to the anamnesis, colic and flatulence were the key symptoms of FGID (p < 0.05). The results show that the formation of FGID in children from birth to 6 months and from 6 to 12 months may be associated with altered colon microbiota. There was a decrease in the quantitative indicators of the indigenous microbiota: bifidobacteria, E. coli with normal sensitivity and Enterococcus spp., and an increase in the degree of contamination of Klebsiella spp., S. aureus, Clostridium spp.Conclusion. It is shown that the determining factor in reducing the risk of developing FGID in children of the first year of life is a high concentration and diversity of indigenous microbiota.